Optimalisasi Pemanfaatan Media Instagram dalam Meningkatkan Hubungan Orangtua dan Sekolah Di Kelompok Bermain Al-Azkia Purwokerto - Abda Billah Faza Muhammadkan Bastian; Wulan Anggraeni (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
In the digital age 4.0, the use of social media for educational purposes needs to be done by educational institutions. Thus, the process of communication and coordination can occur optimally. The purpose of this research is to study the use of Instagram media in KB Al-Azkia. The Al-Azkia KB Public Relations Section carries out management that starts from the planning, implementation and evaluation relating to the use of Instagram media. This research is a qualitative research based on field research. The study was conducted at KB Al-Azkia by obtaining data through observation, interviews and documentation relating to the use of Instagram media. The data validity test is done by triangulation techniques by comparing interview data with observations on Instagram media. The results showed that: firstly, the utilization of the Instagram media began to introduce the Al-Azkia KB institution to the public, so that it could attract students to study there. Secondly, as time goes by, Instagram media is used to report activities to parents and students' assignment results, which they then provide feedback in the form of comments or likes. In this case, the relationship between school and parents of students is increasing Third, management in utilizing Instagram media runs with both starts from the planning, implementation and evaluation. Fourth, KB al-Azkia in uploading photos is always accompanied by good and interesting literacy in Instagram media. Fifth, KB Al-Azkia also utilizes features on Instagram, such as hashtags / labels, geotaging, aroba and photo editing